2016
DOI: 10.1089/ars.2016.6636
|View full text |Cite
|
Sign up to set email alerts
|

Stress Regulates Aquaporin-8 Permeability to Impact Cell Growth and Survival

Abstract: Aquaporin-8 (AQP8) allows the bidirectional transport of water and hydrogen peroxide across biological membranes. Depending on its concentration, H 2 O 2 exerts opposite roles, amplifying growth factor signaling in physiological conditions, but causing severe cell damage when in excess. Thus, H 2 O 2 permeability is likely to be tightly controlled in living cells. Aims: In this study, we investigated whether and how the transport of H 2 O 2 through plasma membrane AQP8 is regulated, particularly during cell st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 62 publications
7
111
0
3
Order By: Relevance
“…Our results confirm previous findings showing suppression of aqp8 gene expression in intestinal inflammatory processes in salmon such as SBMIE [13, 35]. The relation between aqp8 expression and inflammation is consistent with cell-based studies showing that reduced aqp8 expression is linked to increased oxidative cell stress damage [36] and implying that aqp8 is a key player in the maintenance of redox cellular status. DI.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm previous findings showing suppression of aqp8 gene expression in intestinal inflammatory processes in salmon such as SBMIE [13, 35]. The relation between aqp8 expression and inflammation is consistent with cell-based studies showing that reduced aqp8 expression is linked to increased oxidative cell stress damage [36] and implying that aqp8 is a key player in the maintenance of redox cellular status. DI.…”
Section: Discussionsupporting
confidence: 92%
“…The control of H 2 O 2 gradients by peroxiporins (see above) allows for further possibilities of fine-tuning with impact on cell signaling and survival, as shown for AQP8 [98]. AQP3 is required for Nox-derived H 2 O 2 signaling upon growth factor stimulation [99].…”
Section: What Is the Role Of H2o2 In Redox Signaling And Oxidative Stmentioning
confidence: 99%
“…AQP in plasma membranes function as water channels, 27 and it has been shown that AQP 1, 3, 8, and 9 permit the passage of H 2 O 2 . 23,[28][29][30] When the C53S mutation is observed in AQP8, the intake of H 2 O 2 decreases, and it has been reported that this mutation is involved in resistance to oxidative stress. 23 In this study, we looked for the presence of the AQP8 C53S mutation in CRR cells, but results were negative ( Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…AQP8 gene sequencing was performed to detect C53S mutation that had been shown to be resistant to H 2 O 2 treatment. 23 AQP8 gene sequencing showed no evidence of C53S mutation in either CRR or parental cells ( Figure S2(a)-(d)). Results also showed that AQP8 gene expression was downregulated in CRR cells.…”
Section: Aqp8 Mutation and Aqp8 Gene Expressionmentioning
confidence: 99%